Technology tools and approaches to improve undergraduate education (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Developments in science and technology have led to improvements not only in consumable goods but also in teaching and learning in the education sector. Although traditional teaching techniques are still in use, the application of hi-tech and advanced teaching and learning methods is increasing every day. These methods have added new dimensions to teaching and learning. This paper reviews different technology tools and approaches that have been applied to improve teaching and learning in undergraduate engineering education. The findings show that a number of methods have great potential for engineering units but have not been tested yet. Simultaneous applications of these technology tools and teaching approaches will significantly improve the efficiency of both teaching and learning.